2008
DOI: 10.1590/s1413-70542008000600007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação sensorial do café cereja descascado, armazenado sob atmosfera artificial e convencional

Abstract: RESUMOObjetivou-se, com o presente trabalho, avaliar sensorialmente as bebidas e classificar quanto ao tipo o café cereja descascado submetido a diferentes acondicionamentos, ao longo do armazenamento. O experimento foi instalado em delineamento inteiramente casualizado (DIC), em esquema fatorial 2x5x5, com três repetições. Foram testados cinco acondicionamentos, com e sem modificação de atmosfera, em cinco épocas de avaliação, em dois lotes de café cereja descascado, sendo um em pergaminho e o outro beneficia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 0 publications
0
14
0
4
Order By: Relevance
“…Studies have revealed that coffee membranes get damaged at a moisture level of 20% to 30% (w.b.) at temperatures of 60 °C or higher (Borem et al., , , ). Thus, a high drying temperature at the start of the drying process followed by a low range of temperature can be a promising way to maintain coffee quality.…”
Section: Postharvest Processing Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have revealed that coffee membranes get damaged at a moisture level of 20% to 30% (w.b.) at temperatures of 60 °C or higher (Borem et al., , , ). Thus, a high drying temperature at the start of the drying process followed by a low range of temperature can be a promising way to maintain coffee quality.…”
Section: Postharvest Processing Systemsmentioning
confidence: 99%
“…The 60/40 °C treatment (initially 60 °C followed by 40 °C) via hot air shows better results, with lower values for germination, emergence, root protrusion, ESI, and open cotyledonary conditions for natural and washed coffee (Taveira et al., ). This intermediate drying rate also favors the accumulation of high‐molecular‐weight sugars and reducing sugars (Borem et al., , ; Marques et al., ). Coffee layer thickness also matters to the final raw, cup, and total quality of coffee.…”
Section: Postharvest Processing Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the elevated cost, this method has not been viable for many producers (Borém et al, 2008). However, because of the elevated cost, this method has not been viable for many producers (Borém et al, 2008).…”
Section: Effects Of Production and Processingmentioning
confidence: 99%
“…As diferenças na composição química e características dos grãos de café beneficiado, contribuem para que os mesmos, quando submetidos ao processo de torração forneçam bebidas com características sensoriais diferenciadas (BORÉM et al, 2008). As diversas reações pirolíticas que ocorrem durante a torração resultam na degradação, formação e volatilização de vários compostos químicos.…”
Section: Introductionunclassified